Watercolor Painting under the Background of Industrial and Commercial Development in the late Qing Dynasty - Zhu, Yuna (Journal of Education and Educational Technologies, 2023)
In the late Qing Dynasty, Western painting techniques and artistic concepts were gradually introduced into China, which had a profound influence on the development of watercolor painting. This paper will discuss the western influence of watercolor painting in the late Qing Dynasty, including the introduction of Western painting techniques, the promotion of watercolor painting by missionaries and diplomatic missions, and the influence of western artistic concepts on watercolor painters in the late Qing Dynasty. By studying these aspects in depth, we can better understand the background and characteristics of the development of watercolor painting in the late Qing Dynasty.